Simvastatin and ROCK Inhibitor Y-27632 Inhibit Myofibroblast Differentiation of Graves’ Ophthalmopathy-Derived Orbital Fibroblasts via RhoA-Mediated ERK and p38 Signaling Pathways - Wei, Yi-Hsuan; Liao, Shu-Lang; Wang, Sen-Hsu; Wang, Chia-Chun; Yang, Chang-Hao (Frontiers in Endocrinology, 2021)
Transforming growth factor-β (TGF-β)-induced differentiation of orbital fibroblasts into myofibroblasts is an important pathogenesis of Graves’ ophthalmopathy (GO) and leads to orbital tissue fibrosis. In the present study, we explored the antifibrotic effects of simvastatin and ROCK inhibitor Y-27632 in primary cultured GO orbital fibroblasts and tried to explain the molecular mechanisms behind these effects. Both simvastatin and Y-27632 inhibited TGF-β-induced α-smooth muscle actin (α-SMA) expression, which serves as a marker of fibrosis. The inhibitory effect of simvastatin on TGF-β-induced RhoA, ROCK1, and α-SMA expression could be reversed by geranylgeranyl pyrophosphate, an intermediate in the biosynthesis of cholesterol. This suggested that the mechanism of simvastatin-mediated antifibrotic effects may involve RhoA/ROCK signaling. Furthermore, simvastatin and Y-27632 suppressed TGF-β-induced phosphorylation of ERK and p38. The TGF-β-mediated α-SMA expression was suppressed by pharmacological inhibitors of p38 and ERK. These results suggested that simvastatin inhibits TGF-β-induced myofibroblast differentiation via suppression of the RhoA/ROCK/ERK and p38 MAPK signaling pathways. Thus, our study provides evidence that simvastatin and ROCK inhibitors may be potential therapeutic drugs for the prevention and treatment of orbital fibrosis in GO.